SELECTIVE AUTOPHAGY: CAN WE TARGET IT TO EXTEND HEALTH-SPAN?. (11th November 2018) - Cuervo, A
Abstract: Autophagy is an essential cellular process that contributes to maintenance of cellular energetics and protein and organelle quality control. Malfunctioning of autophagy with age may contribute to increase vulnerability to disease in old organisms. In this talk, I will describe the basis for failure of a selective form of autophagy in aging and present the mouse models that we have developed to determine the systemic and organ-specific consequences of autophagy failure. We are currently exploring the potential beneficial effects of preventing autophagy dysfunction with genetic and chemical approaches.